Ruch turystyczny a bezpieczeństwo publiczne na pograniczu polsko-niemiecko-czeskim - Adamczuk, Franciszek (Tourist Movement VS. Public Safety in Polish-German-Czech Border Areas, 2005)
The article refers to safety in tourism. Polish-German-Czech border areas, which constitute the Nyse Euroregion, have been selected as the subject for analysis. The assessment of public safety has been presented, including the safety of tourists in the region and the suggestions for improving the situation in the future. It is one of the first articles referring to this problem in the region and it reflects the topic of the conference held in Jelenia Góra, with Polish, German and Czech specialists participating.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 285-294